Myasthenia Gravis Is Not an Independent Prognostic Factor of Thymoma: Results of a Propensity Score Matching Trial of 470 Patients - Zhai, Yirui; Wei, Yong; Hui, Zhouguang; Gao, Yushun; Luo, Yang; Zhou, Zongmei; Feng, Qinfu; Li, Yuemin (Frontiers in Oncology, 2020)
Objective: The association between the prognosis of thymoma and MG remains controversial. Differences in clinical characteristics and treatments between patients with and without MG may have affected the findings of those studies. We designed this propensity score matching trial to investigate whether MG is an independent prognostic predictor in thymoma.Methods: Patients with pathologically diagnosed thymoma and MG were enrolled in the MG group. Moreover, the propensity score matching method was used to select patients who were diagnosed with thymoma without MG from the database of two participating centers. Matched factors included sex, age, Masaoka stage, pathological subtypes and treatments. Matched patients were enrolled in the non-MG group. Chi-squared test was used to compare the characteristics of the two groups. Overall survival, local-regional relapse-free survival, distant metastasis-free survival, progression-free survival, and cancer-specific survival were calculated from the diagnosis of thymoma using the Kaplan-Meier method.Results: Between April 1992 and October 2018, 235 patients each were enrolled in the MG and non-MG groups (1:1 ratio). The median ages of patients in the MG and non-MG groups were 46 years old. The World Health Organization pathological subtypes were well balanced between the two groups (B2 + B3: MG vs. non-MG group, 63.0% vs. 63.4%, p=0.924). Most patients in both groups had Masaoka stage I-III (MG vs. non-MG group, 90.2% vs. 91.5%, p=0.631). R0 resections were performed in 86.8% and 90.2% of the MG and non-MG groups, respectively (p=0.247). The median follow-up time of the two groups was 70.00 months (MG vs. non-MG group, 73.63 months vs. 68.00 months). Five-year overall survivals were 92.5% and 90.3%, 8-year overall survivals were 84.2% and 84.2%, and 10-year overall survivals were 80.2% and 81.4% (p=0.632) in the MG and non-MG groups, respectively. No differences were found in the progression-free survival, distant metastasis-free survival, and local-regional relapse-free survival between the two groups.Conclusion: MG is not an independent or direct prognostic factor of thymoma, although it might be helpful in diagnosis thymoma at an early stage, leading indirectly to better prognosis.